Girls to the rescue : tales of clever, courageous girls from around the world : Real friends - Lansky, Bruce (Edina, Minnesota : Spotlight : ABDO Publishing Company, 2007)
Original stories from around the world that inspire readers to become a new kind of heroine.
On the way to Broken Bow / Marianne J. Dyson -- Reni and the tiger / Timothy Tocher -- Abbie's light / Tenna Leigh -- Troop 13 to the rescue / Penny Warner -- Treasure beneath the hay / Nancy Alpert Mower -- Firedance / Bonnie Brightman -- Taneya's best shot / Debra Tracy -- Ayasha's arrow / Mary Houlgate.
Keywords: Girls -- Juvenile fiction; Children's stories